An Analysis of the Rug-Washing Ceremony in Mashhad-e Ardehāl, Kāshān - Bidgoli, Sayyed Mahmood Sadat (Journal of Persianate studies, 2020)
Abstract The Iranian religious ceremony of rug-washing (qāli-shuyān), commemorating the martyrdom of Emāmzāda Soltān-ʿAli b. Mohammad Bāqer (d. 734/116), is held every year in the second week of autumn in Mashhad-e Ardehāl, a village of Kāshān, Esfahān Province. This ceremony is unique amongst Twelver Shiʿis for its observance in accordance with the solar calendar rather than the lunar. The objective of the present article is to analyze this ceremony and explain its features. The necessary data for this research have been collected from fieldwork on the historical geography of the region and related historical documents. In the analysis of this ceremony, attention is paid to its time, place, and mode of performance. This study suggests that the rug-washing ceremony is at least partly descended from an ancient Mithraic ritual, to which some Zoroastrian features were added in the pre-Islamic period, such as the limiting of its performance to priests; during the Islamic era, ritual Shiʿi elements were further added thereto. As currently performed, this ceremony, exclusive to Ardehāl and dating to the Qajar and possibly Safavid periods, thus bears certain similarities to rituals performed at Karbalāʾ.